Fiscal Policy and Growth in the Middle East and North Africa Region - Eken, Sena (IMF Working Papers; Working Paper ;, 1997)
Establishing a policy framework to sustain high rates of growth is a major challenge facing the economies of the Middle East and North Africa. Given the strikingly dominant role of governments in these economies, this paper focuses on the contribution of fiscal consolidation and reform toward addressing this challenge. On the basis of an examination of fiscal structures, reform and adjustment efforts, and their growth implications during 1980-95, it concludes that the ongoing process of fiscal reform-aimed at reducing budget deficits, improving the budgetary structure, and enhancing the effectiveness of government interventions-is key to ensuring macroeconomic stability and fostering growth.